Design and Build a Battery Charging Station for Electric Vehicles - Saifullah, Hammam (International Journal of Engineering and Emerging Technology, 2022)
Battery is a medium used to store electrical energy. Currently often found cases about the use of batteries that do not last long. This is because we often forget to turn off the device for charging when charging is complete. So that happens is that charging will continue to work even in an over current or over voltage state. In this system used battery type accu. The input voltage from the system charging is voltage PLN which is lowered by the transformer then rectified by the Uncontrolled Full Wave Rectifier and lowered again by Buck Converter. Method used is constant current constant voltage using PI control for the set point of current and output voltage of Buck Converter. The system used STM32F4 microcontrolleras the central control system. When battery is full the relay will work to stop the process charging then SMS gateway will send a notification that the charging is complete. From the test was found that the relay can disconnect when the input voltage of the buck converter is not according to the design and the relay is also able to disconnect when the battery output current is below 0.34 A to overcome overcharge. The implementation on hardware is in accordance with the plan so that the device can be used for charging with the method constant current constant voltage by maintaining acurrent charging of 1.049 A during the initial process charging and voltage charging of 13.8 V at the end of charging so as to prevent overcharge.